THE TURIY MASSIF, KOLA PENINSULA, RUSSIA: MINERAL CHEMISTRY OF AN ULTRAMAFIC-ALKALINE-CARBONATITE INTRUSION - Dunworth E.A.; Bell K. (My University, 2003)
The Turiy Massif, on the southern coast of the Kola Peninsula, consists of five intrusive complexes containing a variety of carbonatites, phoscorites, melilitolites, ijolites and pyroxenites. Petrographic and mineralogical studies of the different rocks show that the samples are texturally heterogeneous. Minerals including apatite, garnet, magnetite, melilite, mica and pyroxene, show systematic variations in composition relating to the rock type in which they occur. Compositional similarities and/or distinct trends are seen in the mineral compositions within the each of the pyroxenite-melilitolite, and melteigite-ijolite rock series, indicating linked petrogenetic histories within each of the two series. The carbonatites from the northern complex may be related to nearby melilitolites, but the central complex carbonatites and phosocorites do not bear any mineralogical (or isotopic) similarities to any of the silicate rocks within the massif.